2000
DOI: 10.1128/jvi.74.2.796-804.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Genetic Determinants of Rubella Virus Associated with Growth in Joint Tissue

Abstract: Further substitution of the sequence representing nucleotides 1 to 2803 to give a complete Cendehill infectious clone restricted growth in SC by a further 100-fold to less than 10 PFU/ml. This region contains three mutations, at nucleotides 34, 37, and 55, within the 5 stem-loop structure. In conclusion, the Cendehill-specific mutations believed to be determinants of joint cell growth are located in two regions, the 5 nontranslated region and in a sequence that encodes the carboxy-terminal region of p150 exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recently, Lund demonstrated that the growth of rubella virus strains vary in their abilities to replicate and persists in cell cultures derived from human joint tissues, and that this arthrotropism appears to be linked to their association with joint symptoms in vivo (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lund demonstrated that the growth of rubella virus strains vary in their abilities to replicate and persists in cell cultures derived from human joint tissues, and that this arthrotropism appears to be linked to their association with joint symptoms in vivo (13) .…”
Section: Discussionmentioning
confidence: 99%
“…(Lund and Chantler 2000; Mitchell et al 1998) Similarly, rubella vaccine response variability is due, in part, to differences in host genetics. (Jacobson et al 2009; Tan et al 2001) Our lab has identified a number of genes where genetic polymorphisms are associated with vaccine response including: HLA; cytokines and cytokine receptor genes; pattern recognition receptor and antiviral genes; as well as in vitamin receptor and other genes.…”
Section: Introductionmentioning
confidence: 99%